HOW STATISTICAL ANALYSIS CAN SERVE ACCOUNTANTS . - Warriner, Philip (The Accounting Review, 1951)
This article discusses how statistical analysis can serve accountants. Statistical analysis is a highly valuable auxiliary to many professions at the present time. But only in very recent years has its great value as an auxiliary rather than as a profession of itself been particularly realized. It is timely, therefore, to consider whether accounting could generate more power by meshing gears with statistics. This question is made even more opportune by the problems which the rise in the general level of prices has thrust upon accountants. These problem, already urgent, are becoming critical with the resumption of the upsurge in prices and the strong prospect of its continuance. Probably the best place for accountants to start in statistical analysis would be with index numbers. They are constructed by ordinary arithmetical processes and are simple to apply. But what spotlights the importance of index numbers to accountants now is their usefulness for dealing with problems presented by the decline in the value of the dollar. It seems not too much to say that if a substantial proportion of accountants were conversant with index number construction and application, these problems would be more concrete and vivid to the accounting profession than they have been and there would be much more rapid progress in handling them.